CLINICAL OUTCOME OF ANEMIA MANAGEMENT WITH AND WITHOUT TRANSFUSION IN HOSPITALIZED MEDICAL PATIENT - Dr. Manoj Kumar Khandelwal ,Dr Nitesh Soni ,Dr Drishti Soni, Dr Gatha Mohanty ,Dr Suvendu Kumar Hota (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Hospitalised patients frequently suffer from anaemia, which frequently results in morecomplications and longer hospital stays. The conventional treatment has been bloodtransfusions, but conservative methods are becoming more popular due to worriesabout the risks involved. In order to assess the efficacy and safety of non-transfusion